After the end - Mackintosh, Clare (New York : G.P. Putnam's Sons, 2019)
"The breathtaking, emotional new novel from Clare Mackintosh. A story about impossible choices. A story about the strength and fragility of love"--Provided by publisher.
Keywords: Contemporary Women -- Fiction; Literary -- Fiction; Sagas -- Fiction